Transition Metal-Oxo Based Sensing of Chromium (III) Using 1, 2-Hydroxyphenylthiourea in Activator and Surfactant Medium - Sunil, A; Rao, S Jagadeeswara (International Journal of Chemistry and Materials Research, 2014)
1,2-hydroxyphenylthiourea(HPTU) undergoes oxidative dimerisation to form an yellow coloured disulphide in the presence of chromium(III)-oxo species which acts as a catalyst. This catalytic process is enhanced to a great extent in the presence of 1,10-phenanthroline which played the role of an activator and sodium dodecylsulphate as a surfactant. The reaction was monitored at λEx = 416 nm and λEm = 520 nm. The studies reveal that the rate of reaction and the amount of chromium(III) are proportional. This sensing mechanism lead to the development of an analytical method for determination of chromium(III) using photometric and fluorometric techniques. The developed methods were applied for the determination of chromium (III) in plant and waste water samples.